Influence of w/s ratio on alite dissolution and C-S-H precipitation rates during hydration. (August 2020) - Naber, C.; Bellmann, F.; Neubauer, J.
Abstract: The first 24 h of hydration of tricalcium silicate (C3 S) have been studied at varying water/solid (w/s) mass ratios ranging from 0.5 to 10. Gathered data comprise the reaction degree, pore solution concentrations and specific surface area evolution. Combined with interfacial C3 S dissolution rates and C-S-H precipitation rates found in the literature, these data are used to calculate theoretical reaction rates from C-S-H precipitation and C3 S dissolution. Compared with the measured reaction rates, theoretical rates calculated from C-S-H precipitation show a good match, indicating a correct kinetic description of C-S-H precipitation. Theoretical rates calculated from C3 S dissolution are higher than expected during the first hours of hydration which could be explained by the buildup of a metastable hydrate phase barrier. Furthermore, a comparison of the reaction rates shows no effect of the w/s ratio. The Ca concentration evolution indicates a delay of the first portlandite precipitation with increasing w/s ratio.